60.7k views
1 vote
Help with the 2 question .. 20 points

Help with the 2 question .. 20 points-example-1
User Chanlito
by
4.6k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

c = a - 2b

= < 4, 5, 6 > - 2 < 1, 2, 3 > ← multiply each component by 2

= < 4, 5, 6 > - < 2, 4, 6 > ← subtract corresponding components

= < 4 - 2, 5 - 4, 6 - 6 > = < 2, 1, 0 >

| c | =
√(2^2+1^2+0^2) =
√(4+1+0) =
√(5)

-------------------------------------------------------------------------------------------------

sum the product of corresponding components

u.v = (3 × 2) + (- 2 × - 1) + (4 × - 6) = 6 + 2 - 24 = - 16

User Roman Nakutnyi
by
5.3k points